Chemical composition of Prangos ferulacea (L.) Lindl., and Prangos uloptera DC. essential oils and their antifungal activities - Seyedeh Fatemeh Hekmat Zadeh; Maral Gharaghani; Sadegh Nouripour-Sisakht; Damoun Razmjoue (Shahrekord University of Medical Sciences, 2022)
Introduction: Candida albicans is an important opportunistic pathogen that is responsible for most fungal infections in humans. Secondary metabolites are known to be antimicrobial and antifungal agents. This study aimed to investigate the chemical composition of Prangos ferulacea and P. uloptera essential oils and evaluate the sensitivity of four genera of Candida. Methods: After collecting plant samples, their essential oils were extracted by the distillation method, and their components were analyzed using Gas chromatography-mass spectrometry to identify constituents. In total, 48 species of Candida isolated from clinical specimens were examined in this study. The antifungal activities of essential oils of P. ferulacea and P. uloptera were evaluated according to CLSI M27-A3 compared to fluconazole. Results: Out of the two tested plants, P. ferulacea had the lowest minimum inhibitory concentration (MIC) against Candida species. However, MIC of this plant against C. albicans isolates was higher than 0.121 μL/mL non-albicans species. Both plants were able to inhibit non- albicans species with MIC90 values of 0.0097 and 0.039 μL/mL. However, their MIC90 values were less than fluconazole against Candida isolates. Conclusion: The results of this study suggest that P. ferulacea and P. uloptera essential oils might be used as new antifungal agents.